Towards an integrated model: Task-Technology fit in Unified Theory of Acceptance and Use of Technology 2 in education contexts (Journal of Applied Learning and Teaching, 2023)
The Unified Theory of Acceptance and Use of Technology 2 (UTAUT2) model has been widely used to study new technological systems. It has proven to be a robust theoretical framework for predicting users’ intentional use. Although UTAUT2 was intended for commercial use, many later studies have focused on educational technologies like e-learning, learning management systems, mobile learning, e-books and instructional tools. This paper reviews previous work done on the model and proposes a new research model by integrating the Task-technology Fit theory with UTAUT2 to study educational technology acceptance.